2020
DOI: 10.1111/1346-8138.15721
|View full text |Cite
|
Sign up to set email alerts
|

Psychological burden of psoriatic patients in a German university hospital dermatology department

Abstract: Psoriasis has a strong impact on patients' lives and is closely linked to psychiatric disorders such as depression, anxiety and substance-related disorders, especially dependence on alcohol and nicotine. The aim of our study was to systematically assess the psychiatric comorbidity and possible associations between psychological factors, disease severity and dermatology-related quality of life in psoriatic patients from a high-need university hospital dermatology department. Consecutive psoriatic patients (new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
(146 reference statements)
0
10
0
1
Order By: Relevance
“…Based on DLQI but also various patient reported outcomes of interest, including SWLS and happiness, a significant association has been demonstrated between increasing AD severity, disease extent, eczema sites and impaired QoL, particularly social functioning and mental health [99,100,[102][103][104][105]107,[111][112][113]. Studies for PSO provide inconclusive results regarding the association between disease severity and QoL [90,96,98,106,108,[114][115][116][117][118]. However, there is evidence that significant changes in PASI, affected body area and disease localization (e.g., facial or genital involvement) predict the DLQI and psychological and physical QoL [90,96,97,106,[114][115][116].…”
Section: Sociodemographic Clinical and Therapeutic Factors Associated...mentioning
confidence: 99%
“…Based on DLQI but also various patient reported outcomes of interest, including SWLS and happiness, a significant association has been demonstrated between increasing AD severity, disease extent, eczema sites and impaired QoL, particularly social functioning and mental health [99,100,[102][103][104][105]107,[111][112][113]. Studies for PSO provide inconclusive results regarding the association between disease severity and QoL [90,96,98,106,108,[114][115][116][117][118]. However, there is evidence that significant changes in PASI, affected body area and disease localization (e.g., facial or genital involvement) predict the DLQI and psychological and physical QoL [90,96,97,106,[114][115][116].…”
Section: Sociodemographic Clinical and Therapeutic Factors Associated...mentioning
confidence: 99%
“…Acta Derm Venereol 2021 involving mental healthcare professionals whenever necessary (9)(10)(11)(12). This is especially relevant, as some evidence suggests that baseline depression and persistent depression during treatment could be indicative of a less favourable treatment course (14,90).…”
Section: /9 Psoriasis and Depressionmentioning
confidence: 99%
“…Anxiety disorders are prevalent in 7-48% of patients with psoriasis (5,8). Given these high numbers of psychological comorbidities, the integrative management of patients with psoriasis in dermatological practice is essential (9)(10)(11)(12). To this end, the establishment of an easy-to-use screening tool would be an important addition to routine clinical practice, ensuring the detection of affected patients, as these conditions are a major source of disability and may also hamper successful dermatological treatment (13,14).…”
mentioning
confidence: 99%
“… 21 The results of ustekinumab therapy by Abrouk et al 21 had a p value of 0.11 between the two PASI groups, meaning that these results are not statistically significant. And lastly, a study by Sondermann et al 22 demonstrated that patients with a low PASI score (<3) had a mean DLQI score of 3.7 and patients with a high PASI score (≥3) had a mean DLQI score of 13.0 ( p < 0.001). This research demonstrated that a better PASI score for the patient gives a better DLQI score.…”
Section: Discussionmentioning
confidence: 99%